Oral rehabilitation in cleft patients: A literature review (Research, Society and Development, 2023)
Introduction: Cleft lip and palate is a malformation that can be congenital or acquired and is established early within the first weeks of intrauterine life. Its rehabilitation process is complex and time-consuming. Objective: to analyze and understand the oral rehabilitation of cleft patients. Methodology: this is a literary review. The searches for scientific evidence were carried out in the following databases: Virtual Health Library, Scientfic Electronic Library Online and PubMed, using the search terms: Cleft lip and palate, Rehabilitation and Treatment. Results: 3021 articles were initially found. After selection, 6 were suitable for the study objectives, the information was passed on to the collection instrument. The included articles were presented in a summary table and the analysis of the results was carried out in a descriptive way, presenting a synthesis of the studies through comparisons and highlighting the differences and/or similarities. Conclusion: it is concluded that rehabilitation in cleft patients has a range of possibilities.